Alfafetoproteína y su relación en malformaciones congénitas: revisión sistemática - Jimbo Chano, José David (2024)
Congenital malformations are anomalies that can alter organs or systems of the human body, they can develop from the first trimester of gestation or from embryogenesis due to a large number of factors, they are classified into major and minor according to their degree of affectation and are one of the main causes of prenatal death worldwide; alpha-fetoprotein is an oncofetal glycoprotein, produced in the fetal liver and yolk sac, reaches its maximum levels between the 16th and 18th week of gestation, so it is ideal to perform an AFP test within this period of time, this protein tends to be altered in front of any abnormality, complication or malformation in the fetus, serving as an indicator of any abnormality present in pregnancy; For this reason, this research was carried out in order to identify the relationship between alpha- fetoprotein levels and congenital malformations, as well as to determine the population at risk of developing malformations. From the 9 articles included in the present systematic review, it could be evidenced that a large number of cases of chromosomal anomalies present decreased levels, while, abdominal wall defects present elevated levels of alpha-fetoprotein, as well as certain cases of neural tube defects, however, there was presence of congenital malformations in pregnant women where AFP values remained normal due to certain factors such as: gestational age, sample integrity, sample handling and storage, in addition, it could be observed that the group mostly affected by malformations are young pregnant women, under 35 years of age, which may be caused by lack of care during pregnancy, nutrition, exposure to radiation, contamination, contact with teratogenic agents